Law, Power, and Justice: A Quranic Perspective - Bisri, Hasan (TAJDID, 2020)
This article seeks to elaborate on the relationship between law, power, and justice from the Koran perspective. This study makes the Quranic texts its primary source. The study results show that from the perspective of the Koran, a legal system, including an Islamic legal order, must have the spirit to create justice. The realization of social justice is the spirit that underlies the stipulation of law. State power, through the legislative body, which is the institution that is authorized to stipulate law, is obliged to make the principle of justice one of a country’s legal pillars. State power through its judiciary must make “considerations for the sake of realizing justice” in every decision on a legal case.